2023
DOI: 10.3390/antiox12061226
|View full text |Cite
|
Sign up to set email alerts
|

Comment on Villalva et al. Antioxidant, Anti-Inflammatory, and Antibacterial Properties of an Achillea millefolium L. Extract and Its Fractions Obtained by Supercritical Anti-Solvent Fractionation against Helicobacter pylori. Antioxidants 2022, 11, 1849

Abstract: Villalva et al. evaluated the potential utility of an Achillea millefolium (yarrow) extract in the control of H. pylori infection. The agar-well diffusions bioassay was applied to determine the antimicrobial activity of yarrow extracts. The supercritical anti-solvent fractionation process of yarrow extract was made to give two different fractions with polar phenolic compounds and monoterpenes and sesquiterpenes, respectively. Phenolic compounds were identified by HPLC-ESIMS by using the accurate masses of [M−H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Franski and Beszterda-Buszczak [1] report some errors made in the identification of compounds in Achillea millefolium extract by MS/MS analysis included in the supplementary material of our published article [2]. We thank them for the observations, and we are pleased to be able to clarify the doubts from these authors.…”
mentioning
confidence: 86%
“…Franski and Beszterda-Buszczak [1] report some errors made in the identification of compounds in Achillea millefolium extract by MS/MS analysis included in the supplementary material of our published article [2]. We thank them for the observations, and we are pleased to be able to clarify the doubts from these authors.…”
mentioning
confidence: 86%
“…and Bacillus sp. [9][10][11][12][13][14][15][16][17][18]. However, the E layer did not inhibit the growth of P. syringae but decreased the number of cells that were viable.…”
Section: Antimicrobial Properties Analysismentioning
confidence: 99%
“…Achillea millefolium L., sea buckthorn (Hippophae rhamnoides L.), and Hypericum species demonstrate multiple beneficial effects, including anti-inflammatory, antioxidant, diaphoretic, spasmolytic, choleretic, hepatoprotective, antipyretic, analgesic, anticancer, and antimicrobial properties [9][10][11][12]. The extracts of A. millefolium L. flower are rich in flavonoid glycosides, flavonoids, and some other phenolic compounds [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this study, we can conclude that yarrow extracts can be useful against Helicobacter pylori infection. The Villalva’s data have been criticized by Franski and Beszterda-Buszczak [ 21 ]. Although they do not question the quality of the paper, these authors raised questions about the correctness of some compounds identified by Villalva et al However, Villalva clarified all the doubts of Franski and Beszterda-Buszczak in a reply paper [ 22 ].…”
mentioning
confidence: 99%